Development Of Nursing Research In Saudi Arabia: A Review Study (The Review of Diabetic Studies, 2024)
Both production and the caliber of publications can be used to assess nursing research in Saudi Arabia. Clinical, health system, and outcome-based research, education, and administration are now included in the broadened area of scientific inquiry in nursing research. Monitoring the advancement of nursing research in the Kingdom of Saudi Arabia is the primary goal of this study. A thorough analysis of earlier research will be done. This study searched for published nursing publications in Saudi Arabia using keywords and databases such as MEDLINE, CINAHL, and PubMed. After 191 publications were found through the search, 87 of them satisfied the requirements for inclusion and were added to the review.